What are leads and lags? - EINZIG, P. (PSL Quarterly Review, 2014)
The article considers the all important and grossly neglected subject of leads and lags, whose immense influence on trends in the foreign exchange market and on official gold and foreign exchange reserves is not recognized nearly sufficiently. In order to understand the origin, development and abatement of foreign exchange crises the workings of leads and lags must first be understood. Before analysing their effects, however, a more precise and clear definition of lead and lags is required. Here, the author reviews the various definitions, broad and narrow, of leads and lags and highlights the most controversial aspect - whether to include changes in forward exchange covering arrangements. The author argues that in most cases forward operations constitute the most important method of leads and lags and therefore their exclusion is not justified. JEL: F31, F33